GOJEK AS HEROES IN PANDEMIC TIMES (ANALYSIS OF HEALTH CAMPAIGN NARRATIVE IN GOJEK ADVERTISING) - Rina Sari Kusuma; Farra Salsabilla AS (Master of Communication Science Program, Universitas Diponegoro, 2023)
In the conditions of the Covid-19 pandemic, the role of the mass media is very important to inform various things, especially about health messages that must be carried out by the community. There are many advertisements about health protocol campaigns that aim to invite or persuade the public to implement health protocols to avoid Covid-19 and reduce Covid-19 cases in Indonesia. Advertisements about health protocol campaigns that are broadcast are also often made by several parties, such as the government and the private sector. One example of this advertisement is the Gojek Indonesia advertisement. The theory used is narrative theory and Transportation Imagery Model. This study uses a qualitative approach with a narrative analysis method. The data collection technique uses documentation. The research subject is Gojek advertisement. The results showed that the health narrative in Gojek's advertisements during the Covid-19 pandemic persuaded the audience by bringing the audience to an actual or real experience as if the audience played a role in the narrative or story, thereby generating empathy. In addition, Gojek was shown as a Hero character during the Covid-19 pandemic.